5G architectural evolution Option4 technology analysis and deployment suggestions - Songtao GAO; Xiangchen MA; Yiming YU; Du PAN (Dianxin kexue)
Option4 architecture improves 5G network performance by aggregating 4G link capabilities on the basis of 5G SA, while taking into account the existing 4G user experience.It is a potential 5G architecture evolution direction that operators are concerned about.The technical principles of Option4 was introduced, the key performance of Option4 from multiple dimensions was analyzed in detail, the impact of Option4 on the complexity of operation and maintenance was discussed, and 5G Option4 architecture deployment suggestions were proposed.